EFFECT OF CHOLESTEROL LOADED CYCLODEXTRIN ON SPERM TRAITS, CHOLESTEROL CONTENT AND PROTEIN TYROSINE PHOSPHORYLATION IN CRYOPRESERVED BUFFALO BULL SEMEN - SINGH, NAVDEEP; CHEEMA, R S; KUMAR, A; KAUR, M; DHALIWAL, G S (The Indian Journal of Animal Reproduction, 2016)
The present study evaluated the impact of cholesterol loaded cyclodextrin (CLC) supplementation (4 mg/ml of extender) in Tris-citric acid egg yolk extender on sperm motility, viability, membrane integrity, cholesterol content and tyrosine phosphorylation of buffalo bull spermatozoa. Thirty ejaculates from 6 buffalo bulls were included in this study. In treatment group, In CLC supplemented extended semen, percent motility, viability and hypo-osmotic swelling increased (p<0.05) over the control at pre-freeze and post-thaw stage. Post-thaw cholesterol content was high (p<0.05) in CLC supplemented group. The SDS gel electrophoresis and western blotting of buffalo sperm extracts with antiphosphotyrosine antibody indicated phosphorylation of 75, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20 and 17 kDa proteins at tyrosine residue during cryopreservation of buffalo semen. However, supplementation of CLC decreased tyrosine phosphorylation of 75, 65, 55, 50, 35, 25, 20 and 17 kDa proteins with considerable variation in bulls. In brief, supplementation of CLC to extender increases motility, viability, membrane integrity, cholesterol content and decreases protein tyrosine phosphorylation of buffalo spermatozoa.